Identifikasi Miskonsepsi Siswa Materi Usaha dan Energi Menggunakan Five Tier Diagnostic Test - Mufti, Mohammad Bakhit; Sunarti, Titin (Universitas Negeri Surabaya, 2024)
Studying physics requires a good understanding of concepts. However, each student has a different ability to understand physics. The difference in students' understanding ability makes students vulnerable to misconceptions. Misconceptions can occur in all physics materials, such as effort and energy materials. One of the misconceptions of work and energy material is that students assume that when applying force to objects shows work, even though no displacement occurs. Misconceptions can hinder the process of acceptance by students of new knowledge or materials that are interrelated with other materials. Therefore, it is necessary to identify misconceptions and their causes as an initial effort in overcoming student misconceptions. The purpose of this study was to identify students' misconceptions and their causes using the five tier diagnostic test instrument. This research is a quantitative descriptive research by starting with a literature study through research articles, making test instruments, then validating the instrument to state the feasibility of the instrument, then collecting data from class XI students of SMA Negeri 1 Cerme. Student test results were analyzed descriptively and the results showed that the misconceptions of work and energy as a whole showed a percentage of 43%. The most misconceptions occur in question number 11 regarding the concept of work by spring force, while the question items with the least misconceptions are questions number 1, 12, and 15 regarding the concepts of work, power, and potential energy. Identification of the cause of the biggest misconception of effort and energy is due to preconceptions with a percentage of 38%. Based on the results of the study, it can be concluded that the material of work and energy has misconceptions with the most identified causes of misconceptions due to preconceptions.Studying physics requires a good understanding of concepts. However, each student has a different ability to understand physics. The difference in students' understanding ability makes students vulnerable to misconceptions. Misconceptions can occur in all physics materials, such as effort and energy materials. One of the misconceptions of work and energy material is that students assume that when applying force to objects shows work, even though no displacement occurs. Misconceptions can hinder the process of acceptance by students of new knowledge or materials that are interrelated with other materials. Therefore, it is necessary to identify misconceptions and their causes as an initial effort in overcoming student misconceptions. The purpose of this study was to identify students' misconceptions and their causes using the five tier diagnostic test instrument. This research is a quantitative descriptive research by starting with a literature study through research articles, making test instruments, then validating the instrument to state the feasibility of the instrument, then collecting data from class XI students of SMA Negeri 1 Cerme. Student test results were analyzed descriptively and the results showed that the misconceptions of work and energy as a whole showed a percentage of 43%. The most misconceptions occur in question number 11 regarding the concept of work by spring force, while the question items with the least misconceptions are questions number 1, 12, and 15 regarding the concepts of work, power, and potential energy. Identification of the cause of the biggest misconception of effort and energy is due to preconceptions with a percentage of 38%. Based on the results of the study, it can be concluded that the material of work and energy has misconceptions with the most identified causes of misconceptions due to preconceptions.